Modeling of a “Hydrogen Valley” to investigate the impact of a regional pipeline for hydrogen supply - Rosén, Sofia; Göransson, Lisa; Taljegård, Maria; Lehtveer, Mariliis (Frontiers in Energy Research, 2024)
Introduction: The transition towards electrolysis-produced hydrogen in refineries and chemical industries is expected to have a potent impact on the local energy system of which these industries are part. In this study, three urban areas with hydrogen-intense industries are studied regarding how the energy system configuration is affected if the expected future hydrogen demand is met in each node individually, as compared to forming a “Hydrogen Valley,” in which a pipeline can be used to trade hydrogen between the nodes. Method: A technoeconomic, mixed-integer, linear optimization model is used to study the investments in and dispatch of the included technologies with an hourly time resolution, while minimizing the total system cost. Four cases are investigated based on the availability of offshore wind power and the possibility to invest in a pipeline. Results: The results show that investments in a pipeline reduces by 4%–7% the total system cost of meeting the demands for electricity, heating, and hydrogen in the cases investigated. Furthermore, investments in a pipeline result in greater utilization of local variable renewable electricity resources, as compared to the cases without the possibility to invest in a pipeline. Discussion: The different characteristics of the local energy systems of the three nodes in local availability of variable renewable electricity, grid capacity and available storage options compared to local demands of electricity, heating and hydrogen, are found to be the driving forces for forming a Hydrogen Valley.